The Radical Right in Switzerland Continuity and Change, 1945-2000 - Skenderovic, Damir 1965- (Berghahn Books, 2009)
There has been a tendency amongst scholars to view Switzerland as a unique case, and comparative scholarship on the radical right has therefore shown little interest in the country. Yet, as the author convincingly argues, there is little justification for maintaining the notion of Swiss exceptionalism, and excluding the Swiss radical right from cross-national research. His book presents the first comprehensive study of the development of the radical right in Switzerland since the end of the Second World War and therefore fills a significant gap in our knowledge. It examines the role that parties and political entrepreneurs of the populist right, intellectuals and publications of the New Right, as well as propagandists and militant groups of the extreme right assume in Swiss politics and society. The author shows that post-war Switzerland has had an electorally and discursively important radical right since the 1960s that has exhibited continuity and persistence in its organizations and activities. Recently, this has resulted in the consolidation of a diverse Swiss radical right that is now established at various levels within the political and public arena
Description based on online resource; title from PDF title page (publisher's Web site, viewed 07. Nov 2022)
Keywords: Geschichte 1945-2000; HISTORY / Europe / Western; Radicalism -- Switzerland -- History -- 20th century; Right-wing extremists -- Switzerland -- History -- 20th century; Die Rechte; Rechtsradikalismus; Schweiz